Constitutive Expression of GsαR201C in Mice Produces a Heritable, Direct Replica of Human Fibrous Dysplasia Bone Pathology and Demonstrates Its Natural History. (November 2014) - Saggio, Isabella; Remoli, Cristina; Spica, Emanuela; Cersosimo, Stefania; Sacchetti, Benedetto; Robey, Pamela G; Holmbeck, Kenn; Cumano, Ana; Boyde, Alan; Bianco, Paolo; Riminucci, Mara
ABSTRACT Fibrous dysplasia of bone (FD) is a crippling skeletal disease associated with postzygotic mutations (R201C, R201H) of the gene encoding the α subunit of the stimulatory G protein, Gs. By causing a characteristic structural subversion of bone and bone marrow, the disease results in deformity, hypomineralization, and fracture of the affected bones, with severe morbidity arising in childhood or adolescence. Lack of inheritance of the disease in humans is thought to reflect embryonic lethality of germline‐transmitted activating Gsα mutations, which would only survive through somatic mosaicism. We have generated multiple lines of mice that express GsαR201C constitutively and develop an inherited, histopathologically exact replica of human FD. Robust transgene expression in neonatal and embryonic tissues and embryonic stem (ES) cells were associated with normal development of skeletal tissues and differentiation of skeletal cells. As in humans, FD lesions in mice developed only in the postnatal life; a defined spatial and temporal pattern characterized the onset and progression of lesions across the skeleton. In individual bones, lesions developed through a sequence of three distinct histopathological stages: a primary modeling phase defined by endosteal/medullary excess bone formation and normal resorption; a secondary phase, with excess, inappropriate remodeling; and a tertiary fibrous dysplastic phase, which reproduced a full‐blown replica of the human bone pathology in mice of age ≥1 year. Gsα mutations are sufficient to cause FD, and are per se compatible with germline transmission and normal embryonic development in mice. Our novel murine lines constitute the first model of FD. © 2014 American Society for Bone and Mineral Research.